1991
DOI: 10.2307/3283138
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the Intestinal Innervation in Mice Infected with Schistosoma mansoni

Abstract: Schistosomiasis mansoni is a parasitic disease in which granulomas form around schistosome eggs in the liver and intestines. The purpose of this study was to determine the alterations in the intrinsic innervation of the distal ileum and proximal colon resulting from schistosomiasis. Using murine schistosomiasis mansoni, we examined light microscopic preparations stained with osmium-zinc iodide or the dihydronicotinamide adenine dinucleotide: nitro BT oxidoreductase (NADH) method. We also examined specific popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
4
19
2
Order By: Relevance
“…Alterations in the vasculature and innervation of the intestines of infected mice have been reported (Kloetzel 1971, Block 1980, Varilek et al 1991. Death of intestinal neurons is uncommon (Nassauw et al 2001).…”
Section: Extrahepatic Pathologymentioning
confidence: 99%
“…Alterations in the vasculature and innervation of the intestines of infected mice have been reported (Kloetzel 1971, Block 1980, Varilek et al 1991. Death of intestinal neurons is uncommon (Nassauw et al 2001).…”
Section: Extrahepatic Pathologymentioning
confidence: 99%
“…In mammals, the nervous, endocrine, and immune systems cooperate to elicit host responses to the intestinal parasites (Fairweather 1997), and many peptides and amines are involved in the communication among cells of these systems (Blalock 1989, O'Dorisio & Panerai 1990. With reference to mammals, the topic that enteric helminths can affect the distribution of neuromodulators of the host gut and induce host responses has drawn the attention of a number of workers in the recent past (McKay et al 1991, Varilek et al 1991, Foster & Lee 1996, Fairweather 1997. However, to date, there have been only very limited observations on the occurrence and distribution of neuromodulators in the intestine of infected fishes (Maule et al 1989, Dezfuli et al 2000.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…In brown trout from the study area, several nerve fibres positive to the anti-bombesin serum were found in the myenteric plexus, in the muscle layers, and in the connective axis of the intestinal folds. These immunoreactive structures increased in infected fish, especially when Pomphorhynchus laevis was present.In the distal ileum and colon of mice infected with Schistosoma mansoni (Trematoda), focal destruction of nerves in the myenteric plexus occurs and VIP-like immunoreactivity in the nerve fibres near granulomas increases (Varilek et al 1991). Some neuropeptides (e.g.…”
mentioning
confidence: 99%
“…Varilek et al (21) observed that focal granulomas destroy the enteric nerves in mice. Occasionally, neural granulomas were found, especially around the periphery of the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In the distal ileum, the main lesion occurred in the myenteric plexus, while in the proximal colon it occurred in the mucosa and submucosal plexus (22). In chronic forms of schistosomiasis, the colon and the small intestine are attacked by the formation of the inflammatory granuloma (10,(13)(14)(15)(16)21,22).…”
Section: Introductionmentioning
confidence: 99%